Problèmes d’acceptabilité des occurrences relevées dans les corpus informatisés : exemple des prédicats nominaux désignant une propriété ou un trait de caractère - Vetulani, Grażyna (Studia Romanica Posnaniensia, 2023)
In this paper, we present the problems encountered during our research in the field of nominal predication in Polish, in particular concerning nouns referring to properties and character traits. In a previous work on predicates referring to various activities and behaviors, carried out with the use of electronic corpora (the National Corpus of Polish Language, as well as electronic sources available on the Internet), we obtained a dictionary of verb-noun collocations with high lexical coverage comparing to traditional dictionaries (not based on electronic corpus research). Using the same corpus data and methodology as before, we conducted a study of the class of predicative nouns referring to properties and character traits. However, the results obtained following the application of this method proved to be unsatisfactory. In this article, we consider the reasons for this in order to optimize research methods later in our work.